Penggunaan Kalimat Interogatif di Kelas A Sore Semester IV Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas PGRI Pontianak - Fitri Wulansari; Ignasia Vina Winanti; Neli Neli; Remina Remina; Marselinus Pigo (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study discusses the use of interrogative sentences in the learning process in the afternoon class A of the Indonesian Language and Literature Education Study Program at Universitas PGRI Pontianak. Interrogative sentences play an important role in verbal interaction as they are used to obtain information and create effective communication. This research employs a qualitative descriptive approach aimed at describing the forms, types, functions, and politeness aspects of interrogative sentences used by students. The results show that students use interrogative sentences in both total forms (expecting yes or no answers) and partial forms (using question words such as what, who, when, where, why, and how). In addition, the aspect of politeness in questioning is also considered important within the learning context. This study is expected to contribute to the development of communication competence and support more effective and polite Indonesian language learning.